The Mineral Springs of Virginia:: Virginia's Lost Landscape - KATEN, Brian (ARCC Conference Repository, 2019)
In his essay "The 19th Century Rural Landscape: the Courthouse, the Small College, the Mineral Springs, and the Country Store", John Brinkerhoff Jackson stated: "One final southern landscape feature deserves much more study than it has so far received: the watering place or spa or mineral springs.1" This paper presents the nineteenth century mineral springs as a particularly significant yet long neglected Virginia landscape. These mineral springs will be revealed as places of convergence and interest to landscape historians, historical landscape architects, preservationists, and contemporary designers interested in heritage landscapes, healing landscapes and tourism